"When channels interact": how omnichannel interactions are redefining value co-creation - JMOUR , Arij; ELAOUD , Nibrass (Revue Internationale des Sciences de Gestion, 2025)
Building on the dominant logic of service, this article examines the effect of interaction via online and offline channels on consumers' value co-creation behavior. As expected, the results showed a positive effect of interaction with all possible sources on value co-creation. These findings enrich the theoretical understanding of value co-creation and omnichannel behavior. The sample consisted of 387 respondents, of whom 144 were men (37.2%) and 243 were women (62.8%). Data analysis identified three dimensions of interaction: interaction with frontline staff, virtual interaction (social network members/community manager), and interaction with other people (friends/community members/family). The results demonstrate that all three types of interaction have a positive effect on value co-creation. The theoretical and managerial implications, limitations, and future directions of the research are discussed.